Freeze-thaw Effect on the mechanical properties of different wood species: impact of moisture content variations, microscopic morphology, and thermal modification in a selected species - Stephen Asare; Megan Stoescu; Luis Balmori; Srinivas Allena; Emmanuel Kidando; Josiah Owusu-Danquah (Journal of Infrastructure Preservation and Resilience)
Abstract This study investigates changes in the mechanical qualities (such as the deformation capacity, compressive strength, and compressive stiffness) of structural timber due to freezing and thawing cycles. Ten (10) specimens, including nine (9) distinct wood species, were assessed, with one from a thermally modified version of a specific species. The findings indicated that by the end of 60 full freeze-thaw cycles, the mechanical qualities had generally deteriorated for all wood species; however, the rate of reduction in these properties varied depending on the type of wood. The maximum reduction of the deformation capacity was evaluated as 16.2% for Iroko, and the lowest was 0.1% for Mahogany. Again, an average decrease of 29.5% was observed in the stiffness of Mahogany, while the least change in the stiffness was 4% for Soft Maple wood. To expound on the possible changes in the wood surface profile and fibers during freeze and thaw cycles of 20, 40, and 60, a scanning electron microscope (SEM) analysis was also conducted. It was observed that the overall fiber density variation, due to the distribution of developed cracks and pores, accounts for the different responses in each complete set of cycles. Some of the wood species showed a progressive decrease in the fiber density from 0 to 60 freeze-thaw cycles, while others exhibited some surging effects. This explains the possibility of some of the wood’s mechanical properties increasing between cycles of freeze-thaw action (before finally reducing). For the first time, the impact of prior thermal treatment on the freeze-thaw resistance of wood was also investigated. It was seen that thermally modified Red Oak showed improved resistance to freeze-thaw in terms of compressive stiffness when compared to untreated Red Oak. However, the deformation capacity and compressive strength declined in the thermally modified wood compared to the untreated wood.